Ticarcillin Hypersusceptibility in Pseudomonas Aeruginosa in Cystic Fibrosis - IT Hettiarachchi; T O'Sullivan; M Wootton; A Smith; J Duckers; R Dhillon (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2017)
Background: A subpopulation of Pseudomonas aeruginosa (PsA) exists in cysticfibrosis (CF) patients that  is  hypersusceptible  to  ticarcillin,  a  carboxypenicillin,  in  vitro (Tichs strain)  defined  as  a minimum inhibitory concentration (MIC) ≤4μg/ml. Methods: In a retrospective cohort study, isolates of PsA from CF (23),  non-cystic fibrosis bronchiectasis (NCFB) (17) and control (18) patients were analysed. MICs for each isolate were determined using agar dilution against six antibiotics and interpreted using EUCAST breakpoints. Prevalence of Tichs in  each  cohort  was  calculated.  A  point  prevalence  survey  was  conducted  in  CF  to  review  the  patients' clinical progress following PsA isolation. Results: Prevalence of the Tichs strain in PsA was 48%, 76% and 0% in the CF, NCFB and control cohorts respectively. A statistically significant difference in geometric mean MIC was seen between the Tichs and non-Tichs  cohorts in CF for ticarcillin (as expected) and temocillin (p=0.041and p=0.036 respectively). A similar trend was observed in NCFB for ticarcillin (p=0.038) and temocillin (p=0.067), although statistical significance was not reached for the latter.In  CF,  the  Tichs  strain  demonstrated  lower  MICs  to  all antibiotics  tested  apart  from  gentamicin compared  to  their  non-Tichs counterparts. Those  who  had the Tichs strain  in  CF  had  fewer  antibiotics (13.9  days  versus  23.5  days,  Tichs  and  non-Tichs respectively)  although  this  result  was  not  statistically significant p=0.202. Conclusion: Our  data  supports  the  existence  of  a  Tichs strain  of  PsA  in  our  CF  and  NCFB  patient populations. This strain correlated with reduced MICs to temocillin in CF, to which PsA would normally be resistant, which may be of clinical relevance.